y = (x^2 - 1)/x
To find the inverse, swap the x and y variables, and then solve for y.
x = (y^2 - 1)/y
Multiply both sides by y
xy = y^2 - 1
Bring everything to the right hand side.
0 = y^2 - xy - 1
Now, we want to solve this using the quadratic formula. In this case, a = 1, b = -x (the coefficient of y), and c = -1. Therefore
y = [1 +/- sqrt[ (-x)^2 - 4(-1) ] ] / 2
y = [1 +/- sqrt(x^2 + 4)] / 2
Note that, at this point, this is no longer a function. However, we're given the domain of the original function was that x > 0.
One noteable trait about functions and inverses is that they swap domains and ranges, so it follows that the inverse of this function will have a range of y > 0.
To summarize, we have two functions:
y = [1 + sqrt(x^2 + 4)] / 2
There's no doubt that y > 0 in this case.
y = [1 - sqrt(x^2 + 4)] / 2
This case is questionable, however. This cannot happen, and we can prove this by contradiction.
Assume that this can happen. Then
y > 0, so
[1 - sqrt(x^2 + 4)] / 2 > 0.
Multiply both sides by 2,
1 - sqrt(x^2 + 4) > 0
Moving the 1 to the other side,
-sqrt(x^2 + 4) > -1
Now, multiplying both sides by (-1) and flipping the inequality,
sqrt(x^2 + 4) < 1.
Square both sides,
x^2 + 4 < 1, and
x^2 < -3, which is impossible because x^2 is always greater than or equal to 0.
That means we can reject the possibility that
y = [1 - sqrt(x^2 + 4)] / 2
And as a result, our inverse is
y = [1 + sqrt(x^2 + 4)] / 2
2007-01-29 15:44:49
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋